QRIS SHARIA TRANSACTIONS FROM THE PERSPECTIVE OF FIQH MUAMALAH: A STUDY ON THE INTEGRATION OF DIGITAL PAYMENTS AND THE POTENTIAL FOR GHARAR. - Muhammad Imtiaz Humed (Fakultas Agama Islam Universitas Islam Al-Azhar, 2025)
The integration of Sharia QRIS as a digital payment system in the Islamic economic ecosystem presents both opportunities and challenges from the perspective of fiqh muamalah. On the one hand, Sharia QRIS promotes efficiency, security, and financial inclusion; however, on the other hand, issues arise regarding the clarity of contracts, the potential for gharar, and the protection of users' digital rights, which require a comprehensive review of Islamic law. This study uses a qualitative descriptive approach based on literature review to identify the compatibility of the QRIS Syariah transaction structure with Islamic contract principles. The analysis results indicate that the use of QRIS can be considered valid if it meets the elements of information transparency, mutual consent between parties, and a clear contract structure, even in digital form. The potential for gharar can be minimized through the provision of complete transaction descriptions and a fair verification system. Additionally, the implementation of QRIS Syariah based on the values of Maqashid Syariah contributes to the protection of wealth (ḥifẓ al-māl), justice (‘adl), and the public interest (maslahah ‘ammah). Systematic Shariah supervision and education for users are key to ensuring the validity and blessings of Shariah-based digital transactions.